Impact of somatosensory tinnitus and painful temporomandibular disorder in patients with migraine - Camargo, Gabriela Schumacher de; Thaís Spisila; Fontana, Luana Carolina; Jendik, Luana Aparecida; Lima, Ana Carolina da Silva; Rogério Hamerschmidt; Guimarães, Rita de Cássia Cassou; Sydney, Priscila Brenner Hilgenberg (Headache Medicine, 2023)
Full abstract in PDF.